NUTRIENTS CYCLING AND ACCUMULATION IN PEARL MILLET AND PAIAGUAS PALISADEGRASS BIOMASS IN DIFFERENT FORAGE SYSTEMS AND SOWING PERIODS - Costa, Raoni Ribeiro Guedes Fonseca; Severiano, Eduardo da Costa; Costa, Kátia Aparecida de Pinho; Souza, Wender Ferreira de; Brandstetter, Eduardo Valcácer; Castro, Wayron Araújo de; Barbosa Santos, Charles (Scientia Agraria, 2017)
Developed the study objective of was to evaluate nutrient cycling and accumulation in pearl millet and Paiaguas palisadegrass biomass under different forage systems and sowing periods in integrated crop-livestock. The experiment followed a randomized block design with a 5 × 2 factorial arrangement and three replications, under five forage systems (monocropped pearl millet, monocropped Paiaguas palisadegrass, pearl millet intercropped in rows with Paiaguas palisadegrass, pearl millet intercropped between rows of Paiaguas palisadegrass and pearl millet oversown and intercropped with Paiaguas palisadegrass) and in two sowing periods (February and March). The results showed that Paiaguas palisadegrass monocropped or intercropped in rows or between rows, exhibited the highest nutrient cycling and accumulation in the remaining biomass. Nutrient accumulation the under all of the examined forage systems showed the following decreasing order: K > N > Mg > Ca > P > S. Potassium was the nutrient exhibiting the greatest accumulation in the biomass and it exhibited a higher percent decrease with decomposition time. The first sowing period for the forage systems led to higher nutrient cycling and accumulation in the biomass. Intercropped systems through in integrated crop-livestock showed a promising technique to maintain the nutrient cycling and accumulation with sustainability.